Table of Content - - (Journal of Curriculum and Teaching Methodology, 2025)
Table of Content: 1. The extent to which the Kitab al-Tawhid 2 course for the second year of secondary school includes the standards of the Education and Training Evaluation Commission Mr. Abdul-Mohsen Abdullah Al-Harbi ,Prof. Fahd Abdul-Aziz Abanmi 2. The Effect of Using Dual Situated Learning Model (DSLM) to Teach Chemistry in the Development of Conceptual Comprehension of Secondary School Female Students Ms. Ebtisam Ali Hamdi 3. The effect of using the learning-by-play strategy on female students’ achievement in chemistry and their attitudes towards subject Ms. Nadia Obidullah Abu Zaherah ,Eman Khaled Al-Harbi , Lara Ali Al-Shehri 4. The role of the teacher in developing awareness of environmental risks among primary school students in Makkah Al-Mukarramah in light of the cognitive learning theory Mr. Mukhlid Saad Alotaibi 5. The Degree of Islamic Studies Teachers’ Use of Constructivist Theory Principles in Teaching Situations Mr. Ali Atiyah Ali Al-Malki 6. The level of systemic thinking skills (perceiving relationships and structure) in mathematics among female primary school students in Al-Makhwah Governorate Ms. Mona Sultan Musleh Al-Bogami ,Prof. Abdul-Malik Misfer Al-Maliki ,Asst-Prof. Sultan Safar Al-Maliki 7. The effectiveness of using augmented reality technology in raising the on learning mathematics among students with learning difficulties in the third grade of primary school in Makkah Al-Mukarramah Co-Prof. Hanan Ali Bagabas, Ms. Lina Nayef Asiri